2003
DOI: 10.2133/dmpk.18.245
|View full text |Cite
|
Sign up to set email alerts
|

Uptake Mechanism of Pitavastatin, a New Inhibitor of HMG-CoA Reductase, in Rat Hepatocytes

Abstract: To understand the mechanism underlying the highly liver-selective distribution of pitavastatin, uptake experiments were performed using rat hepatocytes. The uptake of pitavastatin into rat hepatocytes is carrier-mediated and involved nonspecific diffusion in the presence of Na(+). The michaelis constant (K(m)) was 26.0 micromol/L, maximal uptake velocity (V(max)) was 3124 pmol/min/mg protein, and non-specific uptake (P(dif)) was 1.16 microL/min/mg protein. There were no remarkable differences in these kinetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 32 publications
(35 reference statements)
3
20
0
Order By: Relevance
“…For CCK8 and deltorphin II in CHO cells the extremely low observed P dif values were, respectively, 0. , 1992;Ismair et al, 2001;Shimada et al, 2003;Lancon et al, 2004;Treiber et al, 2004;Ho et al, 2006). For many transporter model substrates, such as taurocholate and estrone-3-sulfate, which have negligible passive diffusion, this approach is appropriate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For CCK8 and deltorphin II in CHO cells the extremely low observed P dif values were, respectively, 0. , 1992;Ismair et al, 2001;Shimada et al, 2003;Lancon et al, 2004;Treiber et al, 2004;Ho et al, 2006). For many transporter model substrates, such as taurocholate and estrone-3-sulfate, which have negligible passive diffusion, this approach is appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…In hepatocytes, passive processes are typically assessed in a parallel incubation at 4°C to disable any active transport proteins (Komai et al, 1992;Ismair et al, 2001;Shimada et al, 2003;Lancon et al, 2004;Treiber et al, 2004;Ho et al, 2006). However, whereas active transport is inhibited at low temperature, passive processes might also be altered as membrane fluidity decreases (Frezard and GarnierSuillerot, 1998;Neuhoff et al, 2005;Webborn et al, 2007).…”
mentioning
confidence: 99%
“…In the present study, drug associated with the hepatocytes was measured after separation from free drug by layering the suspension of drug and hepatocytes over silicone/mineral oil followed by rapid centrifugation Ϫ the oil-spin method (Petzinger and Fuckel, 1992), a method used by several groups (Ishigami et al, 1995;Nakai et al, 2001;Nezasa et al, 2003;Shimada et al, 2003;Hallifax and Houston, 2006) to characterize hepatic uptake by a clearance term for active transport, CL active , together with K m and V max and a passive permeability parameter, P diff . As enzyme-transporter interplay complicates the interpretation of many of these types of studies, the nonspecific P450 inhibitor, l-aminobenzotriazole (ABT) (Mico et al, 1988), has been used to eliminate any potential metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Shimada et al (2003) have recently reported that the uptake of pitavastatin by rat hepatocytes is saturable and temperature dependent, suggesting that pitavastatin might be transported by carrier-mediated systems. Pitavastatin is scarcely metabolized in human liver microsomes and is excreted into the bile in unchanged form (Kojima et al, 2001).…”
mentioning
confidence: 99%